Computer standards & interfaces. (Amsterdam Elseiver Science Publishers, 1986)
"The quality of software, well-defined interfaces (hardware and software), the process of digitalization, and accepted standards in these fields are essential for building and exploiting complex computing, communication, multimedia and measuring systems. Standards can simplify the design and construction of individual hardware and software components and help to ensure satisfactory inter working."
Keywords: Computers -- Standards -- Periodicals; Computer interfaces -- Periodicals